The perceptions of danish physiotherapists on the ethical issues related to the physiotherapist-patient relationship during the first session: a phenomenological approach - Praestegaard, Jeanette (BioMed Central, 2011)
BACKGROUND: In the course of the last four decades, the profession of physiotherapy has progressively expanded its scope of responsibility and its focus on professional autonomy and evidence-based clinical practice. To preserve professional autonomy, it is crucial for the physiotherapy profession to meet society's expectations and demands of professional competence as well as ethical competence. Since it is becoming increasingly popular to choose a carrier in private practice in Denmark this context constitutes the frame of this study. Physiotherapy in private practice involves mainly a meeting between two partners: the physiotherapist and the patient. In the meeting, power asymmetry between the two partners is a condition that the physiotherapist has to handle. The aim of this study was to explore whether ethical issues rise during the first physiotherapy session discussed from the perspective of the physiotherapists in private practice. METHODS: A qualitative approach was chosen and semi-structured interviews with 21 physiotherapists were carried out twice and analysed by using a phenomenological framework. RESULTS: Four descriptive themes emerged: general reflections on ethics in physiotherapy; the importance of the first physiotherapy session; the influence of the clinical environment on the first session and; reflections and actions upon beneficence towards the patient within the first session. The results show that the first session and the clinical context in private practice are essential from an ethical perspective. CONCLUSIONS: Ethical issues do occur within the first session, the consciousness about ethical issues differs in Danish physiotherapy private practice, and reflections and acts are to a lesser extent based on awareness of ethical theories, principles and ethical guidelines. Beneficence towards the patient is a fundamental aspect of the physiotherapists' understanding of the first session. However, if the physiotherapist lacks a deeper ethical awareness, the physiotherapist may reason and/or act ethically to a varying extent: only an ethically conscious physiotherapist will know when he or she reflects and acts ethically. Further exploration of ethical issues in private practice is recommendable, and as management policy is deeply embedded within the Danish public sector there are reasons to explore public contexts of physiotherapy as well.